Balancing the State and Transnational Corporate Responsibility in the Protection of Transboundary Air Pollution - Abdurrahaman, Ahmad Yahaya; Edward-Ekpo, Cyprian Friday (Center for Law and Responsible Business Studies, 2025)
Transboundary air pollution (TAP) represents a significant global challenge that necessitates a nuanced equilibrium between state responsibility and the accountability of transnational corporations. This scholarly article delves into the intricacies and obstacles inherent in striking this balance, employing a comprehensive examination of case studies, legal frameworks, and international precedents. The central objective of this inquiry revolves around determining the degree to which states and corporations should bear responsibility for transboundary harm as an infringement on Environmental Rights. The renowned Trail Smelter’s case serves as a crucial example, shedding light on the assignment of liability to a privately owned company and the relevance of delving into international liability. This study highlights the Trail Smelter case and other TAP instances, emphasizing their significant role in shaping International Environmental Law (IEL). Despite these notable advancements, the article concludes that challenges persist in addressing TAP. As exemplified in Trail Smelter’s case, beyond the identification of pollution sources, grappling with issues of causation and determining state responsibility proves to be complex, particularly when pollution traverses vast distances, a disconcerting problem arises regarding the direct accountability of corporations for their actions without involving states at the international level. To address this issue, the research recommends enhancing international cooperation via agreements and information-sharing, establishing comprehensive monitoring systems with transparent data reporting, and fostering corporate accountability and sustainable practices through robust national and internal regulatory frameworks. These frameworks should prioritize principles like the polluter pays principle, Equator Principles, Precautionary Principle, and due diligence.